2018
DOI: 10.1002/adom.201800083
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Diiridium Complexes with Bridging Pyrazolates: Characterization and Fabrication of OLEDs Using Vacuum Thermal Deposition

Abstract: efficient and durable emitters that are capable to show RGB colors constitute one of the key components for the successful advancement of OLED technology. [1] However, development of metal based phosphorescent emitters, particularly the blue-emitting phosphors, is still far from success in term of emission efficiency and chemical stability. [2] This is attributed to the higher energy demanded for the excited states of blue-emitting phosphors versus those of the lower-energy green and red emitters, so that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…Both complexes show intense T 1 →S 0 phosphorescence with spectral maxima at λ max =558 nm and λ max = 605 nm for 5 and at λ max =575 nm and λ max = 618 nm for 6, as measured in degassed toluene (c ≈ 10 5 M) at room temperature ( Figure 2). The resulting radiative rate k r = 0.78•10 6 s -1 of 5, calculated as k r = Φ PL /τ, is a high value for phosphorescence although still comparable to other mono-nuclear Ir(III) complexes and even some polynuclear systems reported earlier 27,46 . However, the almost three times larger value k r =2.27•10 6 s -1 of the di-nuclear 6 is remarkable.…”
Section: Optical Spectroscopysupporting
confidence: 82%
See 2 more Smart Citations
“…Both complexes show intense T 1 →S 0 phosphorescence with spectral maxima at λ max =558 nm and λ max = 605 nm for 5 and at λ max =575 nm and λ max = 618 nm for 6, as measured in degassed toluene (c ≈ 10 5 M) at room temperature ( Figure 2). The resulting radiative rate k r = 0.78•10 6 s -1 of 5, calculated as k r = Φ PL /τ, is a high value for phosphorescence although still comparable to other mono-nuclear Ir(III) complexes and even some polynuclear systems reported earlier 27,46 . However, the almost three times larger value k r =2.27•10 6 s -1 of the di-nuclear 6 is remarkable.…”
Section: Optical Spectroscopysupporting
confidence: 82%
“…As a result, complex 6 is an emitter with an emission rate a few times higher than other Ir(III) phosphors used in OLEDs. 10,14,17,19,21,23,[25][26][27][29][30][31][32] Moreover, by the emission rate, 6 also outcompetes the materials exhibiting thermally activated delayed fluorescence (TADF) [62][63][64][65][66][67][68] which are posed as alternative OLED emitters. 62,[69][70][71][72] The proposed di-nuclear design affords outstanding phosphorescence efficiency and also leaves room for photophysical tuning through modifications of the bridging C^NN^C ligand and N^C^N ligand and also through modifications at the position of the halogen anion.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…16). 173 Among them, 149 exhibits blue-shifted emission peaks at 468, 500, and 536 nm due to the combined inductive and mesomeric effects. Importantly, very high PLQYs of >0.90 were observed for all diiridium complexes in both solution and film states at RT.…”
Section: Rigid Structure For Restricted Intramolecular Motionmentioning
confidence: 99%
“…OEs are a rapidly evolving field, but recent developments can be approximately categorized according to their method of exciton recombination: phosphorescence (Ph) and thermally activated delayed fluorescence (TaDF). 32 These categories are thoroughly explored in several reviews [33][34][35] , but we chose to focus on the best-performing materials identified by Bräse et al 32 For OEs, a green, red, and blue chemical substance of each generation were chosen for packages 2-OLED [36][37][38] (Ph) and 3-OLED [39][40][41] (TaDF). It is unclear which alternative substance is used by industry, but we decided to investigate these because of their impressive performance in academic papers.…”
Section: Identify and Screen Alternativesmentioning
confidence: 99%